Green Development of Marine Fishery in Zhoushan City: Status Quo, Challenges and Countermeasures - Chi, Cheng (Journal of Global Economy, Business and Finance, 2025)
As an important base for Chinas marine fisheries, Zhoushan City has achieved significant results in promoting the green development of marine fisheries in recent years. Leveraging its unique marine resources and policy support, Zhoushan City has formed a complete industrial chain that integrates fishing, aquaculture, processing, and sales, with a rich variety of seafood products and stable yields. However, with the over-exploitation of marine resources and increasing environmental pressures, Zhoushan Citys marine fisheries face numerous challenges, such as the decline in fishery resources, ecological pollution, and an unreasonable industrial structure. To address these issues, Zhoushan City has implemented a series of measures, including strengthening the protection of fishery resources, enhancing environmental supervision, and optimizing the industrial structure, aiming to achieve sustainable development in marine fisheries. This paper provides an in-depth analysis of the current status and challenges of green development in Zhoushan Citys marine fisheries, and proposes a series of targeted strategies and recommendations to provide valuable references for the green transformation and development of Zhoushan Citys marine fisheries.